FEA Simulation of the Propagation of Magnetic Field Waves Strength Inside a 275kV Main-Intake Substation - Mohd Sawi@Rahim, Omar Farouq; Baharom, Md Nor Ramdon (Evolution in Electrical and Electronic Engineering, 2022)
High voltage main substation is very important for step-up voltage and step-down voltage. The magnetic fields inside high voltage substations have become a concern in recent days due to the high value of the magnetic field can give a bad effect on human health. The objective of this study is to design an FEA simulation model of the typical 275kV main-intake substation, to profile a propagation of magnetic field wave strength produced by the simulation’s model and to study the magnetic field strengths measured at a ground level according to a different type of condition and situation. ANSYS Maxwell software has been used to measure the magnetic field in five different areas. This software was used to solve electromagnetic field, eddy current and transient current Within a finite region of space, using appropriate boundary conditions. The researcher would focus on the magnetic field (MF) only since the power delivery value is varied depending on the load demand over time. It is related to the current value carried by the busbars. A higher value could be expected during the peak period. Rapid further development of the distribution area would increase the future load demand, hence would cause the lines (busbars) to carry higher currents.  The result of the simulation is showing the magnetic field and was compared between different types of case studies. The result can be concluded that the value of an electric field can change according to conditions and situations. The key findings and outcome from the work would provide valuable information to the authority and the designer/engineer on the matters related to the mentioned modeling of the substation using the Ansys Maxwell software, the FEA magnetic field profiles and analysis of the lines under various working conditions and designs.